Nonlinear optical effects suppression methods in WDM systems with EDFAs: A review - Nordiana, Mohamad Saaid (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/